2012
DOI: 10.1021/jp3066794
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Oxygen Adatoms, Hydroxyl Species and Water Dissociation on Pt(111)

Abstract: Calorimetric measurements of the adsorption enthalpy of O 2,g to make 2 O ad on Pt(111) were performed by Fiorin et al..1 However, we show that they used a calibration value for the optical reflectivity of Pt(111) that was incorrectly reported in the literature. This error in reflectivity led to a 40% error in the adsorption energies originally reported. We use our more accurate reflectivity of 76% to recalibrate their oxygen adsorption enthalpy data and show that it gives nearly identical results below 0.15 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 20 publications
(77 reference statements)
6
84
1
Order By: Relevance
“…Atomic O and H bind in the three-fold hollow sites, while CO is known to bind in the top site [27][28][29] . The adsorption energies for the range of molecules investigated here are presented in Table 1 along with the experimental values taken from 21 (which in turn were obtained from [30][31][32][33][34][35][36][37][38][39][40] ). Our DFT predictions compare quite favorably to experiments (Table 1): the mean deviation is -0.11 eV, the mean absolute deviation is 0.19 eV and the maximum deviation is 0.37 eV, all across a range of adsorption energies from 0 to 3 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Atomic O and H bind in the three-fold hollow sites, while CO is known to bind in the top site [27][28][29] . The adsorption energies for the range of molecules investigated here are presented in Table 1 along with the experimental values taken from 21 (which in turn were obtained from [30][31][32][33][34][35][36][37][38][39][40] ). Our DFT predictions compare quite favorably to experiments (Table 1): the mean deviation is -0.11 eV, the mean absolute deviation is 0.19 eV and the maximum deviation is 0.37 eV, all across a range of adsorption energies from 0 to 3 eV.…”
Section: Resultsmentioning
confidence: 99%
“…It was originally proposed [23], and later corroborated [24], that the reported heats of adsorption for Pt surfaces from the review by Brown et al [7] require a correction factor of 0.71 due to the use of an incorrect optical reflectivity for Pt (which had been reported incorrectly in the prior literature) during data analysis of the reference heats used for calibration. For a more detailed discussion, see reference [24].…”
Section: Establishing the Experimental Databasementioning
confidence: 93%
“…It was originally proposed [23], and later corroborated [24], that the reported heats of adsorption for Pt surfaces from the review by Brown et al [7] require a correction factor of 0.71 due to the use of an incorrect optical reflectivity for Pt (which had been reported incorrectly in the prior literature) during data analysis of the reference heats used for calibration. For a more detailed discussion, see reference [24]. For the Pd(100) surface, we found that the reported heats of adsorption for CO from SCAC were 26 kJ/mol lower than very reliable experimental studies by other methods, which we believe resulted from the same type of error in optical reflectivity (taken from the same prior literature source).…”
Section: Establishing the Experimental Databasementioning
confidence: 93%
See 2 more Smart Citations